EMPLOYING SELF-ASSESSMENT TECHNIQUE TO PROMOTE STUDENT’S WRITING ABILITY IN COMPOSING CAUSE-EFFECT ESSAY AT UNIVERSITAS MUHAMMADIYAH GORONTALO - Indah Wardaty Saud (British : Jurnal Bahasa dan Sastra Inggris, 2019)
This present study aimed to improve students’ writing ability through self-assessment technique. The researcher used an action research method with two cycles. Each of cycle compromised four procedures namely: planning, implementation, observation, and reflection. The data was collected by observation and test. The researcher used an observation sheet towards students and teacher’s activities during teaching and learning process. In addition, the researcher used test to assess students’ achievement in writing. The subject of this study were 25 students of English Literature in Universitas Muhammadiyah Gorontalo who enrolled Essay Writing Subject in academic year of 2016/2017. The result showed that students’ writing ability improved significantly through self-assessment technique. The students had improvement in five aspects such as content, organization, vocabulary, language use and mechanics. The students’ writing average score achieved 86,2. The students’ response towards the technique was good, that the students agree of the benefits they obtained through self-assessment technique.